Steam Boiler Technology for Making Soybean Porridge without Smell of Wood Burning Smoke o Tofu Production - Saputro, Danang Dwi; Sunyoto, Sunyoto; Wicaksono, Dimas; Fibrianti, Nurul (Universitas Negeri Semarang, 2021)
Small industries that make tofu indirectly experience problems in the soybean porridge cooking process. This porridge is the forerunner of tofu. Tofu Serasi Asli product senses an annoying situation to the environment and the development. Furthermore, it is divided into problems of production and management aspects. The boiler design shows that separating the steam production from the pan by flowing saturated steam in each soybean plot. The advantages of using a steam boiler are that the cooking pan does not produce scale and saves time, increases capacity, higher pressure reaches 300 kPa and creates smoke-free kitchen space and a healthier and more hygienic production kitchen. Fuel savings of 48%, an increase in the income of small and medium enterprises and the quality of the tofu produced is better and does not smell of burning smoke.